RESPON SISWA TERHADAP PENGGUNAAN MODEL PBL BERBANTUAN MEDIA FILM DALAM MENINGKATKAN KETERAMPILAN MENULIS TEKS EKSPLANASI - chaniago, Rahma widyanti; Sobari, Teti; Kamaluddin, Tamtam (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Indonesian language learning on writing skills is followed by all students in the class. There is low student interest and ability in writing, finding the main idea and developing an idea, which requires innovation in writing activities. One way to overcome this is by using learning strategies, namely applying the PBL model assisted by film media so that students can observe objects directly and realistically. This research aims to determine students' responses to learning to apply the PBL model assisted by film media on explanatory text writing skills. This research method is descriptive qualitative. The objects in this research were class XI high school students. This research uses a questionnaire as an instrument for collecting data. The results of the research, the distribution of questionnaires distributed to 36 respondents obtained an average percentage of 70.35% in the good category. In this way, students responded well to the application of the PBL model assisted by film media on explanatory text writing skills.